Relationship between Maternal Stress and Neurobehavioral Indicators of Preterm Infants in the Neonatal Intensive Care Unit - Bruna Abreu Ramos; Cibelle Kayenne Martins Roberto Formiga; Nayara Rodrigues Gomes de Oliveira; Patricia Gonçalves Evangelista Marçal; Rui Gilberto Ferreira; Tárik Kassem Saidah; Waldemar Naves do Amaral (MDPI AG, 2024)
Background: Preterm birth and prolonged neonatal hospitalization are potential sources of stress for mothers of preterm and low birth weight infants. Aim: To evaluate maternal stress and its association with neurobehavioral indicators of preterm infants during hospitalization in the neonatal intensive care unit. Methods: A cross-sectional study was conducted in a neonatal intensive care unit of a hospital in Goiânia, Brazil. The study included preterm and low birth weight infants of both genders and their mothers. The Parental Stressor Scale: Neonatal Intensive Care Unit and the Neurobehavioral Assessment of the Preterm Infant were respectively applied to mothers and infants in the neonatal intensive care unit. Results: The study involved 165 premature infants and their mothers. The mean age of the mothers was 26.3 years and most had a high school education level (57.6%). Mothers perceived the experience of having an infant in the neonatal intensive care unit as moderately stressful (2.96 ± 0.81). The parental role alteration (4.11 ± 1.03) and sights and sounds (2.15 ± 0.90) subscales exhibited the highest and lowest stress levels, respectively. Significant correlations (rho < −0.3; p < 0.05) were found between maternal stress and neurobehavioral indicators of infants. In the multivariate analysis, low leg tone was a predictor of higher maternal stress. Low tone and limited arm movement were predictors of higher maternal stress in the maternal role item. Conclusions: The experience of having a preterm infant hospitalized was considered moderately stressful for mothers. Maternal stress levels were significantly correlated with low scores on neonatal neurobehavioral indicators.